Does kinesio taping plus exercise improve pain and function in patients with knee osteoarthritis?: A systematic review and meta-analysis of randomized controlled trials - Wu, Haiyang; Yao, Ruoyu; Wu, Junhao; Wen, Guowei; Wang, Yiru (Frontiers in Physiology, 2022)
Background: Kinesio taping (KT) and exercise are described for improving pain and function of knee osteoarthritis (KOA) patients in most studies. However, the question remains if KT plus exercise is better than only exercise treatment. Objective: To perform a systematic review and meta-analysis of randomized controlled trials (RCTs) to assess the effects of KT plus exercise in improving pain and knee function of KOA patients. Methods: The databases PubMed, Cochrane Library, EMBASE, Springer, web of science and China National Knowledge Internet (CNKI) were searched till July 2022. People diagnosed with KOA were included. The intervention was KT plus exercise, but the comparison group was intervened only with exercise. Outcome measures were the Visual Analogue Scale (VAS) score, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) score, and Timed Up and Go (TUG). Only RCTs were included. The Review Manager software (Version 5.3.5) was used to assess risk of bias, statistical heterogeneity and meta-analysis. Results: The inclusion criteria were satisfied by 642 individuals from sixteen RCTs. There was a significant difference between KT plus exercise group and only exercise group in terms of VAS score after intervention (mean difference (MD)=−0.86; 95% CI=−1.32 to −0.40; P=0.0003). In terms of VAS at follow-up period (MD=−0.58; 95% CI=−1.41 to 0.25; P=0.17), WOMAC score (MD=0.28; 95% CI=−9.16 to 9.71; P=0.95) and TUG after intervention (MD=−0.74; 95% CI=−1.72 to 0.24; P=0.14), no significant difference was found. Conclusion: Although KT plus exercise reduced pain better than exercise, it did not enhance knee function in patients with KOA. These conclusions may change when more high-quality research is conducted. Systematic Review Registration: PROSPERO, identifier: CRD42017060217.